3D printing of tubular scaffolds with elasticity and complex structure from multiple waterborne polyurethanes for tracheal tissue engineering. (September 2018) - Hsieh, Cheng-Tien; Liao, Chao-Yaug; Dai, Niann-Tzyy; Tseng, Ching-Shiow; Yen, B. Linju; Hsu, Shan-hui
Graphical abstract: Highlights: Customized tracheas with cartilage rings are printed from biodegradable PU elastomers. MSCs exhibit chondrogenic differentiation in the rings of the 3D printed trachea. The mechanical properties of 3D printed trachea resemble those of native trachea. The 3D printed trachea is strong to replace native trachea without collapse in vivo. Abstract: A tissue engineering trachea with structural similarity to native trachea was fabricated by the three-dimensional printing (3DP) technique. Two kinds of waterborne biodegradable polyurethanes (PUs) with different physico-chemical properties were used as 3DP ink in this study. The complicated structure of 3DP tracheal scaffolds was fabricated to mimic the structure of native rabbit trachea from the water-based 3DP ink at low temperature. Bioactive factors or small molecular drug (Y27632) could be conveniently incorporated in the ink to promote the chondrogenesis of mesenchymal stem cells (MSCs). The dynamic compression moduli of the 3DP tracheal scaffolds were 0.3–0.8 MPa under the force of 0.1–0.8 N, which resembled those of the native trachea. The airflow test demonstrated the gas tightness of 3DP tracheal scaffolds at both positive and negative air pressures. Moreover, human MSCs seeded in the 3DP tracheal scaffolds displayed the chondrogenic potential and secreted glycosaminoglycans (GAGs) and collagen after 14 days of culture in vitro without exogenous growth factor. The MSC-seeded 3DP tracheal constructs implanted in nude mice for 6 weeks showed a compression modulus similar to that of the native trachea. Meanwhile, MSCs in the scaffolds were grown into cartilage-like tissue. We considered that the 3DP platform of multi-materials and fabrication processes may be employed to produce customized tissue engineering tracheas for future clinical applications.